When Walras meets Vickrey - David Delacrétaz; Simon Loertscher; Claudio Mezzetti (Theoretical Economics, 2022)
We consider general asset market environments in which agents with quasilinear payoffs are endowed with objects and have demands for other agents' objects. We show that if all agents have a maximum demand of one object and are endowed with at most one object, the VCG transfer of each agent is equal to the largest net Walrasian price of this agent. Consequently, the VCG deficit is equal to the sum of the largest net Walrasian prices over all agents. Generally, whenever Walrasian prices exist, the sum of the largest net Walrasian prices is a non-negative lower bound for the deficit, implying that no dominant-strategy mechanism runs a budget surplus while respecting agents' ex post individual rationality constraints.
Keywords: C72; D44; D47; D61; 330; Asset markets; efficient trade; largest net Walrasian prices; VCG deficit